Power scaling analysis of high power fiber laser employing online three-section recoating method of splice point. (28th October 2016) - Huang, Zhihua; Tang, Xuan; Zhao, Pengfei; Li, Chengyu; Li, Qi; Guo, Chao; Li, Zebiao; Lin, Honghuan; Wang, Jianjun
Abstract: Thermal damage is a major limiting factor in the experimental power scaling of high power fiber lasers. A novel online three-section recoating method is proposed in this work which can remove the leaked light due to interface imperfection and improve the heat transfer of the splicing. More than 5.4   k W pump power is injected into the gain fiber through the splice point without damage. Theoretical analysis is carried out with both of the analytical and finite element models. The theoretical results agree in temperature growth slope with the experimental results and the extrapolation implies that it is possible to inject more than 10   k W pump power into the 30/600 YDF from the single end using this method.